Impact of lung function and baseline clinical characteristics on patient-reported outcome measures in systemic sclerosis-associated interstitial lung disease. (31st May 2022) - Kreuter, Michael; Hoffmann-Vold, Anna-Maria; Matucci-Cerinic, Marco; Saketkoo, Lesley Ann; Highland, Kristin B; Wilson, Hilary; Alves, Margarida; Erhardt, Elvira; Schoof, Nils; Maher, Toby M
Abstract: Objective: The SENSCIS ® trial demonstrated a significant reduction of lung function decline in patients with SSc-associated interstitial lung disease (SSc-ILD) treated with nintedanib, but no significant effect on health-related quality of life (HRQoL). To assess whether SSc/SSc-ILD severity and large changes in lung function correlate with HRQoL, a post-hoc analysis of SENSCIS ®, aggregating treatment arms, was undertaken. Methods: Patient-reported outcome (PRO) measures [St. George's Respiratory Questionnaire (SGRQ), Functional Assessment of Chronic Illness Therapy (FACIT)-Dyspnoea, and HAQ–Disability Index (HAQ-DI), incorporating the Scleroderma HAQ visual analogue scale (SHAQ VAS)] at baseline and week 52 were assessed for associations to SSc-ILD severity. Results: At baseline and at week 52, forced vital capacity (FVC) <70% predicted was associated with worse PRO measure scores compared with FVC ≥70% predicted [week 52: SGRQ 45.1 vs 34.0 ( P < 0.0001); FACIT-Dyspnoea 48.9 vs 44.5 ( P < 0.0001); HAQ-DI 0.7 vs 0.6 ( P < 0.0228); SHAQ VAS breathing problems 3.6 vs 2.6 ( P < 0.0001)]. Patients with diffuse cutaneous SSc and other characteristics associated with SSc-ILD severity had worse PRO measure scores. Patients requiring oxygen or with >30% fibrosis on high-resolution computed tomography at baseline demonstrated worse PRO measure scores at week 52. After 1 year, patients with a major (>10%) improvement/worsening in FVC demonstrated corresponding improvement/worsening in SGRQ and other PRO measures, significant for the SGRQ symptom domain ( P < 0.001). Conclusion: Severe SSc-ILD and major deteriorations in lung function have important impacts on HRQoL. Treatments that slow lung function decline and prevent severe SSc-ILD are important to preserve HRQoL. Trial registration: clinicaltrials.gov, www.clinicaltrials.gov, NCT02597933